2014
DOI: 10.1371/journal.pone.0095982
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Nicotine Metabolism of Two Nicotiana attenuata Herbivores Render Them Differentially Susceptible to a Common Native Predator

Abstract: Background Nicotiana attenuata is attacked by larvae of both specialist (Manduca sexta) and generalist (Spodoptera exigua) lepidopteran herbivores in its native habitat. Nicotine is one of N. attenuata's important defenses. M. sexta is highly nicotine tolerant; whether cytochrome P450 (CYP)-mediated oxidative detoxification and/or rapid excretion is responsible for its exceptional tolerance remains unknown despite five decades of study. Recently, we demonstrated that M. sexta uses its nicotine-induced CYP6B46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Hence, that such carcasses were not found on EV or irGGPPS plants, clearly suggested that the BG1-silenced larvae experienced some distinctive predator behaviour. During the night, M. sexta larvae are mainly preyed on by the wolf spiders ( Camptocosa parallela ; Lycosidae), which are abundant in this habitat 32 37 ( Fig. 5d ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, that such carcasses were not found on EV or irGGPPS plants, clearly suggested that the BG1-silenced larvae experienced some distinctive predator behaviour. During the night, M. sexta larvae are mainly preyed on by the wolf spiders ( Camptocosa parallela ; Lycosidae), which are abundant in this habitat 32 37 ( Fig. 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…to evaluate if HGL-DTG co-option has evolved in them; such comparisons between the nicotine metabolism of Manduca spp. and generalist herbivores were highly useful in evaluating the costs and benefits of detoxification and co-option of nicotine 37 . The observation that spiders that ingest BG1-silenced larvae show signs of locomotor distress suggests that Lyc4 affects spider's nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…There are however also insects that perform well on cultivated tobacco, e.g. Helicoverpa zea (Gog et al 2014) and the Hawmoth caterpillar Manduca sexta, that not only tolerates nicotine but even uses the metabolite to deter its natural enemy (Kumar et al 2014).…”
Section: Alkaloidsmentioning
confidence: 99%
“…prot.) [28]; threonine deaminase 2 (TD2) degrades the essential amino acid threonine; the toxic alkaloid nicotine is subject to detoxification by a cytochrome P450 enzyme (CYP6B46) [34]; the maize cysteine protease (Mir1) affects the integrity of the peritrophic matrix, which may be compensated for by the insect by new synthesis of the structure (refill) [18]; insects use multiple strategies to neutralize toxic glucosinolates, including metabolism by sulfatase [74]. being inhibited by Ile.…”
Section: Summary and Perspectivesmentioning
confidence: 99%